COTTON BINDING OF THE QURAN FROM THE EAST COAST MALAY PENINSULA BEFORE 20TH CENTURY: A HISTORICAL STUDY - Ahmad Zakaria, Ros Mahwati (Journal of Al-Tamaddun, 2018)
Cotton is a textile that received high demand throughout the world prior to the 20th century. In the 19th century, the cotton industry reached the Malay world through two routes, firstly via direct trade with India, which had taken place prior to the arrival of Western forces, and secondly, through the East India Company, which turned the colonies under its control into revolutionary markets for British industry. The objectives of this research are 1] to study the source of cotton cloth supplies in Patani and 2] to study the cotton cloth material and the designs used in the Qur’an bindings of Patani before the 20th century. The methodologies used in this study are library research for Patani’s trade history and secondly, a critical observation method to analyse the cotton cloths found in a museum collection. A total of 150 Qur’an manuscript artefacts were used in this study. Each cotton cloth’s design was analysed and divided into categories such as: coloured, striped or patterned with Indian or English influences; based on the motifs used. As results of this study, it was found that 1] the cotton that was used in the Qur’an bindings within this collection mainly came from India and Europe, based on the designs featured on the textile. 2] The cotton designs used in the Qur’an binding process are in line with Islamic principles and apply the concept of moderation to honour the Qur’an as the Sacred Book in their lives.